Hybrid Model of Umrah Logistics Management in the Pre-Departure and Departure Phases: Empirical Evidence at PT Ziarah Hati Nurani Tour and Travel - Ziyadul Muhammad Fikri; Mirza Safiraturrohmat; Habibi Ekatoris Arengga; Muhammad Fathi Farhat; Yunita Ardilla (Dinamis : Journal of Islamic Management and Bussiness, 2026)
Logistics management is a critical aspect in organizing Umrah pilgrimages. This study analyzes the implementation of pre-departure and departure logistics management at PT Ziarah Hati Nurani Tour and Travel using a qualitative case study approach. Data were collected through in-depth interviews and participatory observation of manasik activities and the departure process at Juanda Airport. The findings show that pre-departure logistics is implemented through a multi-layered document verification system and intensified coordination from D-30, while departure logistics is controlled through internal briefings, re-verification, a single Person in Charge (PIC), and layered supervision. This study finds that Umrah logistics operates across four simultaneous dimensions technical-administrative, regulatory-shariah, human-psychological, and adaptive-learning forming a unique hybrid system distinct from conventional logistics. These findings contribute to the development of a logistics management framework within Islamic management scholarship. Keywords: Logistics Management, Pre-Departure, Departure.